Factors affecting resilience of drug abusers at correctional facilities - Warsini, Sri; Astuti, Arfiana Fani; Sari, Diana Nurlaila; Lestari, Pita Puji; Pratiwi, Sherli Damara; Masdar, Mahmasoni; Prasetyo, Nur Ajie; Indriati, Diah Fitri; Marchira, Carla R (MEDISAINS, 2019)
Background: Indonesia is currently facing a narcotics emergency as indicated by a drastic increase in the number of drug users and drug-related deaths. Rehabilitation does not guarantee recovery and relief from drugs. Even while undertaking rehabilitation, drug abusers may relapse. Resilience can prevent drug abusers from relapsing and help them overcome their problems. There has been a dearth of research focusing on factors affecting the resilience of drug abusers in Indonesia.Objective: The objective of this research is to identify factors affecting the resilience of drug abusers at correctional facilities in the Special Region of Yogyakarta.Methods: This is a cross-sectional design and was conducted in February 2017 at the Correctional Facility for Narcotics Cases Class IIA in Sleman and the Correctional Facility in Wirogunan. A total of 77 respondents were involved in this research by a consecutive sampling technique. The instruments used included the resilience questionnaire developed by Pertiwi based on Grotberg’s theory, Beck Depression Inventory II, Satis-faction with Life Scale and Positive Affect Negative Affect Schedule, Isundariyana’s stress instrument, Rosenberg Self-Esteem Scale (RSES), Zung Self Rating Anxiety Scale (ZSAS), General Self-Efficacy Scale, Life Orientation Test-Revised (LOT-R), and Difficulties in Emotion Regulation Scale (DERS). The data were analyzed by univariate, bivariate (Pearson and Spearman’s Rank), and multivariate (linear regression) analyses.Results: Out of the 8 factors examined (subjective well-being, optimism, self-esteem, emotion regulation, anxiety, stress, depression, and self-efficacy) and 2 demographic factors (age and occupational status), only self-efficacy (β = 1.063; p = 0.13), optimism (β = 1.51; p = 0.01), and self-esteem (β = 1.540; p = 0.009) affected resilience.Conclusions: Self-efficacy, optimism, and self-esteem are modifiable factors that can influence the resilience of drug abusers